THE EFFECT OF TALENT MANAGEMENT AND PERCEIVED ORGANIZATIONAL SUPPORT ON EMPLOYEE RETENTION IN PT. PATCO ELEKTRONIK TEKNOLOGI CIBITUNG - Taufiq Rachman; Inna Nisawati Mardiani (SEAN Institute, 2022)
Efforts are made to maintain employee loyalty, namely by implementing employee retention through talent management practices and the role of organizational support. This study uses a quantitative methodology. The population is 303 people, the sampling method uses random probability sampling, with the calculation of the Slovin formula so that 75 people are obtained. Collecting data from observations and questionnaire results. The data analysis tool uses the SPSS version 22.0 program. The results of multiple linear regression analysis and t-test on the talent management variable obtained a value of sig. 0.050 with a standard value of sig. < 0.05, then the value is 0.050 < 0.05, which means that talent management has a significant effect on employee retention. It was explained that the proper application of talent management can increase employee retention. The results of the research on the perceived organizational support variables obtained the value of sig. 0.000 with a standard value of sig. < 0.05, then the value is 0.000 < 0.05, which means that the perceived organizational support has a significant effect on employee retention. It was explained that the perceived organizational support that employees feel through recognition and other support will affect employee retention rates. The results of the coefficient of determination test obtained R = 0.530 > 0.05. and R² = 0.281 indicates that the talent management (X1) and perceived organizational support (X2) together have an effect on employee retention by 28.1%.